Quercus Brantii Lindl. Vaginal Douche Versus Clotrimazole on Vaginal Candidiasis - A Randomized Clinical Trial - - Zeinab Moshfeghy; Khadegeh Asadi; Marzieh Akbarzadeh; Atefeh Zare; Tahereh Poordast; Masoumeh Emamghoreishi; Fatemeh S.Najib; Mehrab Sayadi (Korean Pharmacopuncture Institute, 2018)
Objectives:Vaginal Candidiasis with an approximate prevalence of 30% is the second cause of vaginal infections. Antifungal azole is the first treatment for Vaginal Candidiasis; however, some side effects have been reported for this chemical medicine. Based on the antifungal activity of Inner Stratum of Quercus Brantii (Q. Brantii), the aim of our study was to compare the effects of vaginal douche of Q. Brantii extract and clotrimazole on vaginal candidiasis symptoms before and after the treatments, in women.Methods:89 non-pregnant women with positive KOH test which is capable of identifying the presence of hyphae and mycelium by adding KOH (10%), and a positive vaginal candidiasis culture were randomly divided into two experimental groups, using permuted block randomization method. One group received clotrimazole vaginal cream (1%) and the other group received vaginal douche of Q. Brantii extract. Groups were treated for 7 days and KOH tests and cultures were evaluated again. Data were analyzed via chi-square and independent t-test, using SPSS software.Results:According to the results, there were no significant differences between experimental groups for demographic characteristics like age (p=0.403), BMI (p=0.911), educational levels (p=0.862) and contraceptive methods (p=0.702). Moreover, significant differences were seen in vaginal discharge between the groups after the treatments (P=0.043).Conclusion:The results suggested that the therapeutic effect of vaginal douche of Q. Brantii extract was approximately similar to that of clotrimazole vaginal cream.